Synthesis, characterization and biological studies of organotin(IV) complexes of thiosemicarbazone ligand derived from pyruvic acid : x-ray crystal structure of [Me2Sn(PAT)] - Affan, Md. Abu; Foo, Siong Wan; Ngaini, Zainab; Shamsuddin, Mustaffa (Malaysian Society of Analytical Sciences, 2009)
Six organotin(IV) complexes of pyruvic acid thiosemicarbazone ligand [H2PAT, (1)] with general formula [RSnCln-1 PAT)] [R = Me2, n = 1 (2); R = Bu2, n = 1 (3); R = Ph2, n = 1 (4); R = Me, n = 2 (5); R = Bu, n = 2 (6); R = Ph, n = 2 (7)] were synthesized by direct reaction of thiosemicarbazone ligand (1), base and organotin(IV) chloride(s) in absolute methanol under N2 atmosphere. These organotin(IV) complexes were characterized by elemental analyses, molar conductivity, UV-visible, FTIR, 1 H and 13C NMR spectral studies. Among them, dimethyltin(IV) complex (2) was also characterized by X-ray crystallography diffraction analyses. The cytotoxicity of the ligand (1) as well as its organotin(IV) complexes (2-7) were determined by Artemia salina, shrimp test lethality bioassay